Comparative Evaluation of Recombinant Protein Production in Different Biofactories: The Green Perspective. (12th March 2014) - Merlin, Matilde; Gecchele, Elisa; Capaldi, Stefano; Pezzotti, Mario; Avesani, Linda
Abstract : In recent years, the production of recombinant pharmaceutical proteins in heterologous systems has increased significantly. Most applications involve complex proteins and glycoproteins that are difficult to produce, thus promoting the development and improvement of a wide range of production platforms. No individual system is optimal for the production of all recombinant proteins, so the diversity of platforms based on plants offers a significant advantage. Here, we discuss the production of four recombinant pharmaceutical proteins using different platforms, highlighting from these examples the unique advantages of plant-based systems over traditional fermenter-based expression platforms.